Analisis Makna Kepuasan Hidup Lansia yang Tinggal di Panti Wredha Omega Semarang - Hana Fitri; Selfi Ana Andriyanti; Bunga Kresna Nandini; Siti Nurazizah; Salsabila Atiq Khoirunnisa; Dewi Ambarwati; Naily Yusriah; Nasya Akmala; Siti Hikmah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The increasing number of elderly people living in nursing homes is an important concern, given that their psychosocial and spiritual needs are often not optimally met. This study aims to analyze the life satisfaction of elderly people living in Omega Nursing Home in Semarang City. The main reason for this research is to understand in depth how the elderly make meaning of their lives and the satisfaction of life that has passed before, in situations that are often far from family and meaningful activities. This study used a qualitative method with a phenomenological approach, and involved 5 elderly participants selected through purposive sampling technique. Data were collected through in-depth interviews, then analyzed descriptively through the process of data reduction, data presentation, and conclusion drawing. The results showed that the level of life satisfaction of the elderly varied greatly and was influenced by past experiences, acceptance of current conditions, expectations for the future, and the views of others. Some seniors showed resignation, regret and loneliness, while others felt comfortable, grateful and retained a zest for life. The main findings suggest that social relationships, spirituality, and communication with family are key determinants in shaping older adults' life satisfaction. This study emphasizes the important role of the nursing home in facilitating activities that build the social and spiritual relationships of the elderly, as well as the need to improve communication between the elderly and their families. The study suggests that elderly services should not only focus on physical needs, but also on psychosocial dimensions and self-actualization, to support the overall well-being of the elderly.